Ultra-broadband optical amplification using nonlinear integrated waveguides - Ping Zhao; Vijay Shekhawat; Marcello Girardi; Zonglong He; Victor Torres-Company; Peter A. Andrekson (Nature, 2025)
Abstract Four-wave mixing is a nonlinear optical phenomenon that can be used for wideband low-noise optical amplification and wavelength conversion. It has been extensively investigated for applications in communications 1 , computing 2 , metrology 3 , imaging 4 and quantum optics 5 . With its advantages of small footprint, large nonlinearity and dispersion-engineering capability, optical integrated waveguides are excellent candidates for realizing high-gain and large-bandwidth four-wave mixing for which anomalous dispersion is a key condition. Various waveguides based on, for example, silicon, aluminium gallium arsenide and nonlinear glass have been studied 6–10 , but suffer from considerable gain and bandwidth reductions, as conventional design approaches for anomalous dispersion result in multi-mode operation. We present a methodology for fabricating nonlinear waveguides with simultaneous single-mode operation and anomalous dispersion for ultra-broadband operation and high-efficiency four-wave mixing. Although we implemented this in silicon nitride waveguides, the design approach can be used with other platforms as well. By using higher-order dispersion, we achieved unprecedented amplification bandwidths of more than 300 nm in these ultra-low-loss integrated waveguides. Penalty-free all-optical wavelength conversion of 100 Gbit s −1 data in a single optical channel of over 200 nm was realized. These single-mode dispersion-engineered nonlinear waveguides could become practical building blocks in various nonlinear photonics applications.